Mechanism of mitral regurgitation in hypertrophic obstructive cardiomyopathy - Pridie, R. B. (1970)
Echocardiography of the mitral valve in patients with hypertrophic obstructive cardiomyopathy has revealed an abnormal pattern of movement. The abnormality is characteristic, readily recognized, and can be explained in anatomical and physiological terms. It consists of a sharp reopening of the valve during systole when it should normally remain in the fully closed position. This abnormal movement mirrors the mid-systolic onset of both outflow tract obstruction and mitral regurgitation. It was only absent in the two patients with the disease in whom both mitral regurgitation and outflow tract obstruction were also absent. A second and less striking abnormality was a reduced diastolic closure similar to that seen in mitral stenosis and attributed to slow left ventricular filling. The echo from the septum is also unduly prominent.